2016
DOI: 10.17221/209/2015-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Freezing and storage of leukodepleted erythrocyte suspensions

Abstract: Studies on the frozen storage of human blood products have benefited veterinary transfusion medicine in recent years, but the long-term cryopreservation of canine red blood cells (RBCs) has not yet been thoroughly investigated. Further, no studies are available with respect to the frozen storage of leukocyte-depleted canine red blood cells (LD-RBCs). The objective of the current study was to investigate time-dependent effects of long-term frozen storage on leukocyte-depleted canine RBCs. Twelve healthy adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
1
3
0
1
Order By: Relevance
“…[6][7][8][9][10][11][12] Canine cryopreservation techniques have also been successfully described in three previous reports using modifications of both automated and manual human protocols. [19][20][21][22] However, our findings are consistent with a recent study 23 that evaluated glycerol and HES as cryoprotectants for both canine and feline pRBCs. This study reported that neither HES nor glycerol were able to cryopreserve and recover feline RBCs successfully.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…[6][7][8][9][10][11][12] Canine cryopreservation techniques have also been successfully described in three previous reports using modifications of both automated and manual human protocols. [19][20][21][22] However, our findings are consistent with a recent study 23 that evaluated glycerol and HES as cryoprotectants for both canine and feline pRBCs. This study reported that neither HES nor glycerol were able to cryopreserve and recover feline RBCs successfully.…”
Section: Discussionsupporting
confidence: 90%
“…[9][10][11][12][13][15][16][17][18][19][20][21][22] In developing the protocol used in this study, we found that the materials and methods sections of the various publications had limited details related to each protocol, especially the manual techniques involved. [9][10][11][12][13][15][16][17][18][19][20][21][22] For instance, while Contreras et al described in detail the manual thawing and washing protocol for cryopreservation of canine pRBCs with glycerol, their protocol did not describe the method of agitation used when adding glycerol to the RBCs. 19 In addition, while Contreras et al used an automated RBC processor for the washing steps, Kim et al did not detail the washing steps in their protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contáctenos: rev.med.ucr@gmail.com pacientes sometidos a procedimientos cardíacos se ha visto una disminución de las lesiones por reperfusión al reducir la activación de los neutrófilos, la producción de superóxido, complemento y leucotrienos después de la restauración del flujo sanguíneo [28,29 Los pacientes con enfermedad renal en etapa terminal experimentan barreras creadas por la aloinmunización. Esto se ejemplifica por el hecho de que aproximadamente el 30% de los candidatos a trasplantes renales en lista de espera están sensibilizados.…”
Section: Beneficios No Comprobadosunclassified